Quantifying the CaO and CaF2 Content of Industrial Ladle Furnace Slag with Optical Emissions Measured through the Casting Spout. Issue 5 (27th October 2021) - Pauna, Henri; Aula, Matti; Huttula, Marko; Fabritius, Timo
Abstract : CaO and CaF2 are important slag constituents and additive materials in secondary metallurgy. Optimization of the quantity of these compounds has a key role in adjusting the slag chemistry for optimal refining properties. Herein, the CaO and CaF2 content of the slag is analyzed with optical emissions from an industrial ladle furnace measured through the casting spout. Molecular optical emissions from CaO and CaF are observed directly from the molten bath and the arc, whereas atomic emission lines from the slag components are detected in the arc spectra. Optical emissions from CaO, CaF, and atomic calcium lines are correlated with the CaO and CaF2 content of the slag. The CaO and CaF2 content of the slag could be evaluated from the spectra ranging from 10 to 41 min before the X‐ray fluorescence (XRF) analysis is finished. The mean differences between the optical emission spectroscopy (OES) and XRF analysis are 0.59% and 0.61% for CaF2 and 2.19% and 0.67% for CaO when using the spectra from the molten bath and the arc, respectively. The method has the potential to work as an in situ online measurement system due to real‐time data acquisition and fast computation times. Abstract : In situ optical emission spectroscopy is used to study light emitted by the arc and the molten bath through the ladle furnace's casting spout. With this method that is viable also for online analysis, molecular optical emissions from CaO and CaF together with atomic emissions are used to derive correlations between the spectra and the slag's CaF2 and CaO content.